Impact of the COVID-19 pandemic on the production and sales of cars in the world - Shevchenko, I. Y.; Dmytriiev, I. A.; Dmytriieva, O. I.; Шевченко, І. Ю.; Дмитрієв, І. А.; Дмитрієва, О. І. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. The global automotive industry has already had an experience of recovery from the global financial crisis of 2008, but the pandemic crisis of 2020 is quite different in nature and pattern of progress: in recent history it has had no analogues and it will be premature to state its completion. Therefore, it is important to determine the impact of the pandemic on the production and sale of cars in order to overcome the negative consequences. To address this issue, the article identifies the sensitivity of this subsector of mechanical engineering to destructive changes in the environment; an analysis of changes in the volume of production and sales of cars by countries of the world over the past period has been made. Goal. The aim of the work is to determine the destructive consequences and trends of the COVID-19 pandemic impact on the global automotive industry, namely the production and sale of cars. Methodology. To determine the impact of the COVID-19 pandemic, a vertical and horizontal analysis of car production and sales in the world has been conducted. Results. The results of the analysis allowed the authors to group the countries of the world by the destructive effects of the pandemic crisis of 2020 for the automotive industry. Originality. The carried out classification of countries by the destructive effects of the COVID-19 pandemic provided an opportunity to gain insight into its impact on the automotive industry, in particular on the production and sale of cars. Practical value. The obtained results can be recommended to identify further ways to overcome the negative effects of the COVID-19 pandemic in the automotive industry.
Вплив пандемії COVID–19 на виробництво та продажі автомобілів у світі
Keywords: automotive industry; socio–economic development; car production; car sales; COVID–19 pandemic; автомобільна індустрія; соціально–економічний розвиток; виробництво автомобілів; продаж автомобілів; пандемія COVID–19; 339.9; 10.30977/AT.2019–8342.2021.49.0.06